Analysis of User Satisfaction with the KAI Access Application Using the Technology Acceptance Model (TAM) - Lubis, Farach Nur Fachri; Nasution, Muhammad Irwan Padli; Nurbaiti (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
The aim of this research is to examine the variables that influence user satisfaction with the KAI Access application at PT Kereta Api Indonesia. The data collection method used an online questionnaire distributed to individuals using the KAI Access application in Binjai City. Data analysis was conducted using the Technology Acceptance Model (TAM). The research findings indicate that user satisfaction with the application increases because it is easy to use, which in turn boosts users' intention to continue using it in the future. Additionally, PT KAI (PERSERO) has the capability to conduct ongoing user research to address any issues users encounter while using the KAI Access application. The purpose of this research is to identify the challenges users face when using digital applications in the transportation industry and to provide guidelines for improving user satisfaction.